Penerapan Datamining Menentukan Minat Baca Mahasiswa Di Perpustakaan Universitas Bina Darma Palembang Menggunakan Metode Clustering - Lemi Iryani (INTECOMS: Journal of Information Technology and Computer Science, 2020)
Abstract : This study was conducted to determine student interest in reading in the library Bina Darma with clustering method. The data used in this study is Bina Darma library database that consists of three tables are tables collection, patron tables and tables of visitors who will be selected to be integrated and combined as a data warehouse. Application of data mining to determine the titles of the most demanding of students and courses are most borrowed books and read a book in the library building dharma. The information obtained is that the course is more interested in information systems to borrow and read books compared to the industrial engineering courses. Titles that most interest is the title of the book basics of programming, while the lowest book is the title of students interested in a practical handbook using Microsotf word and cluster categories of books that most interest students are computer science book category books category Indonesian whereas lower. Keywords : Clustering, Data Mining, Data Warehouse, Visitor, Collection, Dan Patron.